CeO2 Supported Gold Nanocluster Catalysts for CO Oxidation: Surface Evolution Influenced by the Ligand Shell. Issue 14 (18th May 2022) - Truttmann, Vera; Drexler, Hedda; Stöger‐Pollach, Michael; Kawawaki, Tokuhisa; Negishi, Yuichi; Barrabés, Noelia; Rupprechter, Günther
Abstract: Monolayer protected Au nanocluster catalysts are known to undergo structural changes during catalytic reactions, including dissociation and migration of ligands onto the support, which strongly affects their activity and stability. To better understand how the nature of ligands influences the catalytic activity of such catalysts, three types of ceria supported Au nanoclusters with different kinds of ligands (thiolates, phosphines and a mixture thereof) have been studied, employing CO oxidation as model reaction. The thiolate‐protected Au25 /CeO2 showed significantly higher CO conversion after activation at 250 °C than the cluster catalysts possessing phosphine ligands. Temperature programmed oxidation and in situ infrared spectroscopy revealed that while the phosphine ligands seemed to decompose and free Au surface was exposed, temperatures higher than 250 °C are required to efficiently remove them from the whole catalyst system. Moreover, the presence of residues on the support seemed to have much greater influence on the reactivity than the gold particle size. Abstract : Heterogeneous CO oxidation : A ligand effect was observed in heterogeneous CO oxidation by Au nanoclusters after oxidative pretreatment at 250 °C, with thiolate‐protected clusters showing significantly higher conversion than phosphine‐protected clusters, for which ligand residues blocked the active interfacial sites.